Covid-19, Knowledge Production and the (Un)Making of Truths and Fakes. Issue 3 (3rd July 2021) - Ogola, George
ABSTRACT: The Covid-19 pandemic is one of the most disruptive phenomena of our time. It has threatened and destabilised the normative, it has stoked fear and anxiety, and laid bare the fragility of our systems of governance, medical science and the immanent tensions within our knowledge systems. The pandemic has provoked a fundamental collision of these systems, leaving in its wake confusion as we struggle over meaning; the production of meaning, its husbandry and political instrumentalisation as a tool for domination and resistance. This article explores the emerging reconfiguration of the certainty about what is authentic or the truth, and of the un/certainty of the fake and fakery as alternative or complementary sites of truth(s). It argues that we are now faced with a complex and layered contestation over who gets to define the truth and the fake, and under what terms. This conversation is deeply insurrectional for it invites the whole world, centres and margins alike, to confront how political, cultural, economic and social values and structures of knowledge production are implicated in the making and unmaking of the authentic, of truth as well as of the fake.